Staging Difficult Pasts Transnational Memory, Theatres, and Museums - Delgado, Maria; Kobialka, Michal; Lease, Bryce (Taylor & Francis, 2024)
This collection of original essays brings together museum, theatre, and performance case studies with a focus on their distinctive and overlapping modes of producing memory for transnational audiences. Whether this is through narrative, object, embodied encounter or a combination of the three, this volume considers distinctions and interactions between memory and history specifically through the lenses of theatre and performance studies, visual culture, and museum and curator studies. This book is underpinned by three areas of research enquiry: How are contemporary theatre makers and museum curators staging historical narratives of difficult pasts? How might comparisons between theatre and museum practices offer new insights into the role objects play in generating and representing difficult pasts? What points of overlap, comparison, and contrast among these constructions of history and memory of authoritarianism, slavery, colonialism, genocide, armed conflict, fascism, and communism might offer an expanded understanding of difficult pasts in these transnational cultural contexts? This collection is designed for any scholar of its central disciplines, as well as for those interested in cultural geography, memory studies, and postcolonial theory. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-NoDerivatives (CC-BY-ND) 4.0 license.